New Coach, New Risks? Injury Trends in Elite Football After Coaching Changes During an Eight-Season Period - Ante Bandalovic; Šime Veršić; Jaksa Skomrlj; Toni Modric; Arian Skoki; Lejla Obradovic Salcin; Ante Turic; Boris Becir; Bruno Lukšić (Applied Sciences)
Although the effect of coach turnover is often discussed within the football community, there is a very limited body of knowledge on this topic. This study aimed to explore which coaching turnovers are associated with changes in injury incidence in an elite professional football club. A longitudinal study observed injury occurrence across the eight-season period, with the team experiencing 16 coaching changes, averaging 2 per season. All injuries were continuously monitored regularly recorded and saved in the club’s database. They were analyzed over three-time frames: for each season, 2 weeks after the coach was sacked, and also for 4 weeks after the coaching change. A paired sample t-test was used separately for the overall injuries and specifically for muscle injuries in the observed time frames. Overall injuries had an increase of 27.7% and 35.4% in the two and four weeks after coaching turnovers, respectively, while for muscle injuries, these rates were lower and amounted to 5.5% and 8.1%. There were no statistically significant changes, but a medium effect size was reported when comparing overall injuries in 4 weeks and the season in general. Muscle injuries appear to be less negatively affected by coaching changes. Club coaching and medical staff should be especially careful in controlling the training load and recovery techniques in the transition periods while also maintaining the club’s preventive methodology.